2010
DOI: 10.1158/1535-7163.mct-09-0694
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Tumor Angiogenesis by the Matrix Metalloproteinase–Activated Anthrax Lethal Toxin in an Orthotopic Model of Anaplastic Thyroid Carcinoma

Abstract: Patients with anaplastic thyroid carcinoma (ATC) typically succumb to their disease months after diagnosis despite aggressive therapy. A large percentage of ATCs have been shown to harbor the V600E B-Raf point mutation, leading to the constitutive activation of the mitogen-activated protein kinase pathway. ATC invasion, metastasis, and angiogenesis are in part dependent on the gelatinase class of matrix metalloproteinases (MMP). The explicit targeting of these two tumor markers may provide a novel therapeutic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…This unique system relies upon proteolytic activation by tumor over-expressed proteases, MMPs and uPA, and we and others have demonstrated that administration of these protease-activated PrAg derivatives, in conjunction with various cytotoxins, can be used to elicit significant in vivo anti-tumor responses in diverse cancer models including melanomas, carcinomas and sarcomas (Alfano et al, 2010; Liu et al, 2003b; Liu et al, 2008; Rono et al, 2006; Schafer et al, 2011; Su et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This unique system relies upon proteolytic activation by tumor over-expressed proteases, MMPs and uPA, and we and others have demonstrated that administration of these protease-activated PrAg derivatives, in conjunction with various cytotoxins, can be used to elicit significant in vivo anti-tumor responses in diverse cancer models including melanomas, carcinomas and sarcomas (Alfano et al, 2010; Liu et al, 2003b; Liu et al, 2008; Rono et al, 2006; Schafer et al, 2011; Su et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Employing this principle, we have previously generated versions of PrAg requiring activation by MMPs (PrAg-L1) (Liu et al, 2000), uPA (PrAg-U2) (Liu et al, 2001), or co-localized MMP/uPA activities (IC-PrAg, consisting of two separate proteins, PrAg-L1-I210A and PrAg-U2-R200A) (Liu et al, 2005). Multiple studies have been performed, as summarized in Table 1, demonstrating that when these engineered PrAgs are co-administered with various cytotoxins, that significant anti-tumor activity towards established tumors can be achieved in a variety of syngraft, xenograft and orthotopic models, highlighting the potential broad-spectrum therapeutic utility of these agents (Alfano et al, 2010; Liu et al, 2003b; Liu et al, 2005; Liu et al, 2008; Rono et al, 2006; Schafer et al, 2011; Su et al, 2007; Wein et al, 2013). These toxin combinations exert there anti-tumor effects through a variety of means including both direct tumor cell killing and killing of cellular components of the tumor stroma, including tumor vasculature (Alfano et al, 2008; Alfano et al, 2010; Liu et al, 2003b; Liu et al, 2008; Schafer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The efficient endosomal escape of lethal factor and edema factor has been used for the delivery of fusion proteins containing the protective antigen-binding moiety of lethal factor to deliver other enzymes to the cytosol. These fusion proteins have been successfully utilized for various tumor-therapy approaches [30,42,43], the delivery of reporter proteins [44] and the delivery of anti-apoptotic Bcl-x L [45].…”
Section: Endosomal Escapementioning
confidence: 99%
“…The elevated expression of certain matrix metalloproteases in the tumor environment can be utilized to activate the toxins at the tumor site [30] and their use in combination with other strategies present attractive possibilities. For instance, targeted protein toxins can be administered as an adjunct treatment for surgery or directly when combined with radio-or chemotherapy [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Coadministration of HuArgI (Co)-PEG5000 with L-citrulline may improve the therapeutic index by protecting normal tissues unable to rescue arginine from ornithine. Furthermore, because amino acid depletion can induce cell cycle arrest, protein synthesis inhibition, and apoptosis, we measured the inhibition of both cellular DNA and protein synthesis, as well as overall growth inhibition measured by metabolic conversion of tetrazolium salt to a formazan [19,29].…”
Section: Introductionmentioning
confidence: 99%